The effect of outdoor learning model on improving cognitive ability in entrepreneurial learning at the field of electricity - Eva Monika Nahulae; Zamtinah Zamtinah (Journal of Education and Learning (EduLearn), 2020)
Outdoor learning model of learning is one alternative to reduce the level of saturation in learning, especially learning the practice in vocational high schools. Outdoor learning models can connect students to deal directly with the world of entrepreneurship so that teachers can teach entrepreneurial values easily. Outdoor learning can link the theories in the book and the reality in the field. The experience gained from the learning process outdoor learning has a lot of influence on student learning outcomes because it can hear, observe and feel direct events that occur in the real world. This study aims to determine the quality of entrepreneurial learning outcomes and their effectiveness by using an outdoor learning model for electricity power expertise students in vocational high school. The study was conducted using a quasi-experimental approach with methods of pretest-posttest control group design. The population of this research was the eleventh-grade students majoring in electrical power installation engineering at SMK Negeri 2 Medan. The sample used in this study were 76 students chosen at randomly. The instrument used in this study was a multiple-choice test. The instrument that was used in this research, previously validated by experts of theory and material. The analysis was performed with the t-test and Gain N-score. This research shows that students who learn to use outdoor learning model was better than students who learn to use conventional model.